Day 3 Thu, March 16, 2017 2017
DOI: 10.2118/184694-ms
|View full text |Cite
|
Sign up to set email alerts
|

World First Closed Loop Downhole Automation Combined with Process Automation System Provides Integrated Drilling Automation in the Permian Basin.

Abstract: Objectives/Scope Today, during the development of unconventionals and particularly in the challenging rock of the Permian Basin, a lack of knowledge about the downhole environment creates a culture of conservatism where excessive safety margins need to be applied to prevent damage to the rig equipment, drill bits, and sensitive drilling tools. Due to varying crew capabilities, inconsistent performance is the norm and lessons learned are poorly implemented on each rig and across the fleet. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The application of standardized procedures under the protection of SOE and FDM functions have shown that automated drilling operations were both possible [5] and increased the efficiency [6]. Attempts have been made to integrate downhole measurements from high-speed telemetry in a closed loop control architecture [7,8]. Also, the control of drilling parameters has been automated using closed loop control [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The application of standardized procedures under the protection of SOE and FDM functions have shown that automated drilling operations were both possible [5] and increased the efficiency [6]. Attempts have been made to integrate downhole measurements from high-speed telemetry in a closed loop control architecture [7,8]. Also, the control of drilling parameters has been automated using closed loop control [9,10].…”
Section: Introductionmentioning
confidence: 99%